The Frequency and Predictors of Sexual Dysfunction Among People Living with HIV/AIDS - Abdu Z; Dule A; Habib S (HIV/AIDS: Research and Palliative Care, 2023)
Zakir Abdu,1 Aman Dule,1 Sadik Habib2 1Department of Psychiatry, Mattu University, Mattu, Oromia, Ethiopia; 2Department of Family Health, Mattu Health Science College, Mattu, Oromia, EthiopiaCorrespondence: Zakir Abdu, Tel +251913845371, Email zakirabdu45@gmail.comBackground: The frequency of sexual dysfunctions reported by HIV/AIDS patients is significantly higher than that of their peers. Sexual dysfunction and its predictors may result in increased viral loads, worsening HIV infection, and infectivity. To mitigate its consequences, appropriate evaluation and intervention are required.Methods: A cross-sectional study design was conducted among 336 HIV/AIDS-positive individuals at one hospital in southwest Ethiopia. To assess sexual dysfunctions, a tool called the Changes in Sexual Functioning Questionnaire (CSFQ-14) was used. Data analysis was done with SPSS version 20. Bivariate and multivariable logistic regressions were used to identify independent predictor variables, and statistical significance was declared at a p-value of < 0.05.Results: 98.53% of the sample completed the questionnaire accordingly. The frequency of SD was 72.0% (95% CI = 67.4– 77.0). The frequency of SD was reported to be more prevalent among males (76.8% (95% CI = 70.6– 81.6)) than that of females (66.2% (95% CI = 59.5– 73.5)). Among the domains of sexual dysfunction, sexual pleasure problems (96.70%, (95% CI: 94.60– 98.50)) were the higher figure of SD, and sexual desire problems (82.40%, (95% CI: 78.60– 86.60)); were the least prevalent sexual dysfunctions. Predictors of the SD were age, social anxiety, nicotine use, poor sleep quality, and time of resuming ART medication.Conclusion: The frequency of SD was 72.0%. Predictors of the SD were age, social anxiety, nicotine use, poor sleep quality, and time of resuming ART medication.Keywords: SD, PLWH, Ethiopia